2016
DOI: 10.1371/journal.pone.0160760
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infections in Medical Intensive Care Units of a Medical Center in Southern Taiwan: Variable Seasonality and Disease Severity

Abstract: Critical patients are susceptible to Clostridium difficile infections (CDIs), which cause significant morbidity and mortality in the hospital. In Taiwan, the epidemiology of CDI in intensive care units (ICUs) is not well understood. This study was aimed to describe the incidence and the characteristics of CDI in the ICUs of a medical center in southern Taiwan. Adult patients with diarrhea but without colostomy/colectomy or laxative use were enrolled. Stool samples were collected with or without 5 ml alcohol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…We found that 435 of 267,871 (0.16%) critically ill patients developed CDI. This was lower than the previously reported rate (14/1488 (0.9%)) in Taiwan [ 27 ]. However, because of the different sample populations and different methodologies used, the incidence rate in the present study might be reasonable.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We found that 435 of 267,871 (0.16%) critically ill patients developed CDI. This was lower than the previously reported rate (14/1488 (0.9%)) in Taiwan [ 27 ]. However, because of the different sample populations and different methodologies used, the incidence rate in the present study might be reasonable.…”
Section: Discussioncontrasting
confidence: 77%
“…A dramatic and significantly higher (2–4 times) incidence of CDI was reported in the past decade in North America [ 25 , 26 ]. The reported incidence of CDI in North American and European ICUs is 0.4–4% of the ICU population [ 27 ]. We found that 435 of 267,871 (0.16%) critically ill patients developed CDI.…”
Section: Discussionmentioning
confidence: 99%
“…A few other studies in humans and food have reported possible C. difficile seasonality. In previous studies in hospitals in Taiwan and Australia, the incidence of CDI was found to be highest in March and lowest in the last quarter of the year (Lee, Hung, Lin, Tsai, & Ko, ; Worth, Spelman, Bull, Brett, & Richards, ). A further review on CDI seasonality reports a similar seasonal pattern in the Northern and Southern hemispheres, with a peak in spring and lower frequencies in summer and autumn (Furuya‐Kanamory et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…A comparable pattern is observed in Asia (3%) and Europe (1%) (32). Additionally, investigations have revealed that 3.6%, 3.3%, 3.3%, 2.4%, 0.9%, and 20% of CDAD in hospitalized patients of the USA, UK, Canada, China, France, and Taiwan are associated to C. difficile infection, respectively (33)(34)(35). The prevalence of CDI or CDAD has been less studied in Iran.…”
Section: Discussionmentioning
confidence: 84%